Computer Image Processing System Based on Feature Extraction Technology - Luo, Xiaojing; Cai, Guangxing (Journal of physics. Conference series, 2021)
This article studies the methods of computer image acquisition, processing and recognition. The study found that the images collected from the computer image processing system often have blurring phenomenon. For this reason, the paper proposes a wavelet transform feature extraction algorithm based on colour images, which can separate the image and the background without greying the colour image. Through experimental research, it is found that this method can efficiently and quickly solve the problem of automatic image registration.